Pharmacokinetics and Pharmacodynamics of a 13-mer LNA-inhibitor-miR-221 in Mice and Non-human Primates - Maria Eugenia Gallo Cantafio; Boye Schnack Nielsen; Chiara Mignogna; Mariamena Arbitrio; Cirino Botta; Niels M Frandsen; Christian Rolfo; Pierosandro Tagliaferri; Pierfrancesco Tassone; Maria Teresa Di Martino (Elsevier, 2016)
Locked nucleic acid (LNA) oligonucleotides have been successfully used to efficiently inhibit endogenous small noncoding RNAs in vitro and in vivo. We previously demonstrated that the direct miR-221 inhibition by the novel 13-mer LNA-i-miR-221 induces significant antimyeloma activity and upregulates canonical miR-221 targets in vitro and in vivo. To evaluate the LNA-i-miR-221 pharmacokinetics and pharmacodynamics, novel assays for oligonucleotides quantification in NOD.SCID mice and Cynomolgus monkeys (Macaca fascicularis) plasma, urine and tissues were developed. To this aim, a liquid chromatography/mass spectrometry method, after solid-phase extraction, was used for the detection of LNA-i-miR-221 in plasma and urine, while a specific in situ hybridization assay for tissue uptake analysis was designed. Our analysis revealed short half-life, optimal tissue biovailability and minimal urine excretion of LNA-i-miR-221 in mice and monkeys. Up to 3 weeks, LNA-i-miR-221 was still detectable in mice vital organs and in xenografted tumors, together with p27 target upregulation. Importantly, no toxicity in the pilot monkey study was observed. Overall, our findings indicate the suitability of LNA-i-miR-221 for clinical use and we provide here pilot data for safety analysis and further development of LNA-miRNA-based therapeutics for human cancer.